High School Algebra Students Busting the Myth about Mathematical Smartness: Counterstories to the Dominant Narrative "Get It Quick and Get It Right" - Teresa K. Dunleavy (MDPI AG, 2018)
This article continues to challenge the robust myth that mathematical smartness is exemplified in individuals who consistently complete mathematics problems quickly and accurately. In so doing, I present a set of counterstories from three students in one ninth-grade Algebra 1 classroom. These students described transformative experiences in their perceptions of mathematical smartness. Analysis of interviews revealed four themes about their perceptions of mathematical smartness, including: (1) consistently and unapologetically affording time and space to value multiple solution strategies, (2) belief in mathematical justification and explanation as the goal for demonstrating mastery of mathematical content, (3) valuing mathematically valid ideas from all class members, and (4) valuing collaborative problem solving as a way to help group members, distribute mathematical knowledge and orient students toward learning with one another. I found that their interpretations of mathematical smartness are counter to the still-dominant myths around speed and accuracy. While the four themes that emerged have been previously studied in the frame of teacher practices, this research provides needed additional empirical evidence of students’ voices describing what mathematical smartness can and should look like.